Tae-Hwan Kwak, Soon Sung Cho y Shannon McCune (Eds.) U.S. Korean Relations, 1882-1982. Seoul, The Institute of Far Eastern Studies, IFES Research Series núm. 17, Kyungnam University, 1982. 433 pp. - Romero Castilla, Alfredo (Estudios de Asia y África, 1986)
-